THE NEW HYPERSPECTRAL SENSOR DESIS ON THE MULTI-PAYLOAD PLATFORM MUSES INSTALLED ON THE ISS - R. Müller; J. Avbelj; E. Carmona; A. Eckardt; B. Gerasch; L. Graham; B. Günther; U. Heiden; J. Ickes; G. Kerr; U. Knodt; D. Krutz; et al. (The International Archives of the Photogrammetry, Remote Sensing and Spatial Information Sciences, 2016)
The new hyperspectral instrument DLR Earth Sensing Imaging Spectrometer (DESIS) will be developed and integrated in the Multi-User-System for Earth Sensing (MUSES) platform installed on the International Space Station (ISS). The DESIS instrument will be launched to the ISS mid of 2017 and robotically installed in one of the four slots of the MUSES platform. After a four month commissioning phase the operational phase will last at least until 2020. The MUSES / DESIS system will be commanded and operated by the publically traded company TBE (Teledyne Brown Engineering), which initiated the whole program. TBE provides the MUSES platform and the German Aerospace Center (DLR) develops the instrument DESIS and establishes a Ground Segment for processing, archiving, delivering and calibration of the image data mainly used for scientific and humanitarian applications. Well calibrated and harmonized products will be generated together with the Ground Segment established at Teledyne. The article describes the Space Segment consisting of the MUSES platform and the instrument DESIS as well as the activities at the two (synchronized) Ground Segments consisting of the processing methods, product generation, data calibration and product validation. Finally comments to the data policy are given.